Aplikasi E-Archiving dan Monitoring Surat Menyurat - Kaban, Roberto; Simbolon, Marice Hotnauli; Abdullah, Abdullah (LPPM UNIKA Santo Thomas Medan, 2019)
A neat and easily monitored-mails administration is an urgent needs of every agency, including UPT. Taman Budaya in Dinas Kebudayaan dan Pariwisata Provinsi Sumatera Utara. Manually archieved-mails generated problems; such as slow disposition, difficulties in tracing the mails, as well as taking a long time to find certain mails required. The proposed application aims to solve those limitations of manual system applied. The Bootstrap CSS Framework is chosen to be applied for its open source and ability to create an easily displayed web in all of gadgets specifications, whereas the methodology used to develop the web system is Web Development Life Cycle (WDLC). This methodology has five stages which are (1)Planning, (2 )Analysis, (3) Design and Development, (4) Testing, and (5) Implementation and Maintainance. The output of this research is an applicable web system that manage mails administration; including disposition, archieving, and monitoring.